Clinical and MRI Donor-Site Outcomes After Autograft Harvesting From the Medial Trochlea for Talar Osteochondral Lesions: Minimum 5-Year Clinical Follow-up. Issue 9 (5th September 2022) - Guo, Changjun; Li, Xingchen; Zhu, Yuan; Yang, Chonglin; Xu, Xiangyang
Background: Autologous osteochondral transplantation (AOT) is a treatment option for large or cystic osteochondral lesions of the talus (OLTs), with promising clinical results. However, donor-site morbidity (DSM) has always been a concern with this procedure. Purpose: To investigate the clinical and radiological outcomes of autograft harvesting from the medial trochlea for OLTs. Study Design: Case series; Level of evidence, 4. Methods: A total of 46 consecutive patients were included after AOT procedures for OLTs, with donor autografts (single or double plugs) harvested from the medial trochlea of the ipsilateral knee. Lysholm scores were collected postoperatively at 12-month intervals to assess clinical outcomes. Postoperative magnetic resonance imaging (MRI) was used to assess the donor site using the MOCART (magnetic resonance observation of cartilage repair tissue) score. DSM was evaluated at 12-month intervals. Statistical analysis was performed to compare patients treated with single-plug and double-plug AOT procedures and establish whether there was any correlation between MOCART and Lysholm scores. Results: The mean follow-up period was 98.3 months (range, 67-144 months). The Lysholm scores for all patients were 92.5 ± 6.1 and 99.9 ± 0.2 at the 12-month and final follow-ups, respectively. MRI of the donor sites was taken at an average of 93.8 ± 20.5 (range, 61-141) months postoperatively, and the mean MOCART score was 76.2 ± 4.9. The overall incidence of DSM in this study was 4.3% at 12 months, postoperatively, which decreased to 0% at the 24-month follow-up. There was no significant difference in either the Lysholm score ( P = .16) or the MOCART score ( P = .83) between the single-plug and double-plug groups at the final follow-up. There were no significant correlations between MOCART and Lysholm scores and patient age, number of grafts, or body mass index. Conclusion: According to the study findings, the DSM of donor autografts harvested from the medial trochlea was low, and the number (single or double) of grafts did not affect the functional outcome.